Idiopathic orbital disease and corticosteroids as first-line treatment: literature review - I. A. Levashov; A. A. Yarovoy (Лечащий Врач, 2021)
Orbital inflammation may occur as local manifestation of systemic disease, in infections, neoplasms and as idiopathic process. Development of new therapeutic modalities requires more fundamental comprehension of the disease and collaboration with other medical specialists, especially rheumatologists and transplantologists.